“O filho que ninguém quer?” : o processo da implementação da comissão de heteroidentificação na UFMT no contexto das relações étnico-raciais brasileiras - Freitas, Évellyn Thaís Peixoto de (2021)
This research is linked to the Nucleus of Studies and Research on Racial Relations and Education - NEPRE, to the Research Line Social Movements, Politics and Popular Education of the Graduate Program in Education of the Institute of Education of the Federal University of Mato Grosso - UFMT. Its object is the analysis of the process of implementation of the hetero-identification committee for admission to undergraduate courses at UFMT-Cuiabá. The general objective is to analyze the process and dynamics of the implementation of the commission of hetero-identification for the admission of black and mixed race students to UFMT undergraduate courses in the context of Brazilian ethno-racial relations: examine the planning and administrative organization of UFMT related to the implementation of the commission of hetero-identification for admission to the selection process of undergraduate courses at UFMT; analyze the effects produced by the implementation of the commission of hetero-identification for the admission of black and mixed race students to undergraduate courses at UFMT; and to understand the perspectives on the implementation of the commission of hetero-identification from the black and brown and white applicants who had their enrollment accepted or rejected by the hetero-identification commission. The problematic of the research asks what are the social, political and pedagogical consequences that the committee of heteroidentification causes in the admission of black and mixed race candidates, in the context of ethnic/racial relations in the UFMT? To what extent is the committee of hetero-identification a necessary mechanism for the implementation of Law No. 12.711/2012, in the context of ethnic-racial relations? How and what forms of functioning of this commission are processed? Our main theoretical contributions on ethnic-racial relations are: Paixão (2014), Guimarães (2009), Domingues (2004); Gomes (2001), Petruccelli (2013), Santos (2016) among others. The study will follow a qualitative research approach, according to Minayo (1999) and Richardson (1999), because we will seek to dive into the research universe in order to achieve the study objectives in order to detail and deepen the data thus highlighting their meanings. The Bardin (1977) content analysis method is used, since it is a set of techniques that aim to systematically describe the messages that were obtained through data collection. Data were produced through the following research instruments: semi structured interviews, participant observation and documents related to the implementation of the hetero-identification committee at the UFMT, such as edicts, news in newspapers, minutes, among others. The research points out that the implementation of the commission of hetero-identification at UFMT was driven by the complaints of people linked to the Black Social Movements and the Student Movement of fraud in the quota system. We observed that the UFMT was reactive to the denunciations so that it could then implement the hetero identification committee. The interviews pointed out that the committee for hetero identification is the "ugly child" or the "child that nobody wants" of UFMT, in general terms, because it is not configured as a process without administrative and social relevance, but within this dynamic it is expected that the University rethinks and re-signifies its administrative and pedagogical actions aiming at the institutional alignment with the agendas about racial issues in an organized and institutionalized way. It was pointed out that the commission of hetero-identification is a necessary mechanism for the effectiveness of the Law No. 12.711/2012, because it constitutes a monitoring policy in the entrance of the candidate in order to avoid fraud or reduce and overcome racial injustices. Finally, the commission of hetero-identification has a pedagogical role in placing popular debate on the content of ethical-racial relations, sometimes contrary to quotas and the commission of heteroidentification, but demonstrating that Law 12.711/2012 is a right.